A cross-sectional and histological analysis to understand the cytological effects of cell phone radiation on buccal mucosa of children - Voleti Sri Srujana Aravinda; Chaitanya Ram Kandregula; Radhika Muppa; M Madhavi Krishna; B S Nikitha; Malathi Yenni (Wolters Kluwer Medknow Publications, 2022)
Context: The ongoing pandemic has affected all the spheres of life and one of the severely affected avenues is the education of a child. The online education has seen an upward curve since the start of COVID-19 pandemic. Schools globally have adopted online class tutorials as the main method to impart education and directly increasing the screen time for a child. Aim: The aim of the present study was to evaluate the cytological effects of prolonged mobile phone usage on the buccal mucosa of children. Settings and Design: Stratified sampling was used for the selection of subjects for the study. After a questionnaire regarding the usage of a mobile phone was distributed among the parents of children. Among them, 90 children were selected on the basis of pattern and frequency of mobile phone usage in the child. Materials and Methodology: The children were divided into three groups based on the per day hours of viewing of mobile phone, i.e., Group 1: Usage of 1-2 h a day, Group 2: Usage of 3-6 h a day, and Group 3: Usage of >6 h a day. The time frame taken into consideration was 1 year after the pandemic started. This was specifically to understand the impact of the online education. Swab was obtained by using the conventional ice-cream stick method from the buccal mucosa. Statistical Analysis: The samples were subjected to histological and microscopical analysis to observe for cytological changes. One-way ANOVA was used to determine the statistical significance if any. Results: The results obtained clearly showed that Group 3 (>6 h usage per day) showed the highest number of cellular and chromosomal aberrations which was significant. Conclusion: The results indicated that impact due to the prolonged screen time on the buccal mucosa is significant. A direct proportionality was seen between the apoptotic changes and chromosomal aberrations and the number of daily hour usage.